When the Ground Drops - Müller, Simone M. (Lagoonscapes)
Focused on a massive sinkhole in Winter Park, Florida of 1981, the article investigates evolving human environment relationships within Central Florida’s karst environments as an interplay of logics and logistics of above and below ground. The article argues that these relationships are formed both in acute situations due to the pressures of increasing urbanization and groundwater extraction in the twentieth century and over the course of millennia due to long-term karst formation processes. The piece focuses on the different types of property damage caused by the sinkhole and introduces insurance companies as guardians of above-ground order. It illustrates that, although the sinkhole briefly overpowers the above-ground logic, it ultimately does not distort existing social inequality. Using the sinkhole as an interscalar vehicle, the article shows the intersection of the horizontal and vertical planes and with it the volumetric intersection of place, space, and time.